CONVERSION OF LAPAROSCOPIC APPENDECTOMY TO OPEN APPENDECTOMY IN CHILDREN REASONS AND CLINICAL OUTCOMES - KHAN, MJ; KARAMATULLAH, .; ULLAH, I; KHAN, MQ (Biological and Clinical Sciences Research Journal, 2023)
This study was carried out To assess the impact of this conversion on clinical outcomes to better understand the reasons for pediatric patients' open appendectomy procedures as opposed to laparoscopic ones. This medical research study is retrospective. We conducted a retrospective study of pediatric patients (ages 1 to 18) who had appendicectomies at MMC Mardan's Department of Pediatric Surgery between January 2010 and December 2020. Patient demographics, preoperative presentation, surgical technique (open or laparoscopic), conversion reasons, intraoperative findings, postoperative problems, duration of hospital stay, and follow-up results were all recorded. The statistical analysis included logistic regression analyses, t-tests, and chi-square tests when appropriate. The research included 462 pediatric patients, of whom 268 had a laparoscopic appendectomy, and 194 underwent open appendectomy. In 56 patients (20.9%), laparoscopic Conversion to open appendectomy was necessary. The most frequent causes of Conversion were adhesion-related vision difficulties (33.9%) and complex appendicitis (46.4%). Compared to patients who had a successful laparoscopic operation, those who had laparoscopic-to-open Conversion had a substantially greater risk of postoperative problems (24.1% vs. 8.2%, p < 0.001) and longer hospital admissions (mean 4.7 vs. 2.9 days, p < 0.001). The results of a logistic regression study showed that older age (OR 1.22, 95% CI 1.06-1.41) and complex appendicitis (OR 3.14, 95% CI 1.56-6.33) were independent predictors of Conversion. In children, complex appendicitis and intraoperative complications often need Conversion from laparoscopic to open appendectomy. Extended hospital stays and a greater incidence of postoperative complications are linked to these patients. Optimizing results and reducing the need for Conversion need a surgeon with extensive training and expertise in patient selection.